Stevens Johnson syndrome following paraquat poisoning: a case report - Shah, Aalap J.; Lakhani, Jitendra D.; Vaswani, Vivek (International Journal of Research in Medical Sciences, 2020)
Paraquat is a herbicidal agent used extensively, mainly in developing countries where there is a high incidence of its poisoning. It causes damage to kidneys, lungs and liver. Reports of mucocutaneous manifestations following paraquat ingestion are rare. Here we describe a case of Stevens-Johnson syndrome(SJS) presenting in a case of paraquat ingestion. A 22 year old male was admitted to our hospital for difficulty in swallowing and micturation since ingestion of 10-15 ml of paraquat 7 days before. He had multiple hemorrhagic crusted erosions over lips and left maxillary area with diffuse erythematous erosions over bilateral buccal mucosa, palate, labial mucosa and urethral mucosa with whitish slough over them. Upper GI endoscopy revealed oral, esophageal and fundal sloughing. Patient was treated with oral corticosteroids and antibiotics which caused complete resolution of skin lesions within 15 days. Paraquat dichloride exerts its toxicity by generation of reactive oxygen species. Skin lesions following topical application of paraquat are common, but very few cases have been reported of the same after oral ingestion. SJS is caused by a variety of drugs and commonly presents with muco-cutaneous tenderness, hemorrhagic erosions and erythematous macules with 90% developing oral, genital and gastrointestinal mucosal involvement. As the oral and genital manifestations in our patient developed the day after paraquat ingestion, possibility of SJS developing due to the same are the highest. Paraquat should not be ruled out as a drug causality if mucocutaneous manifestations of SJS/TEN appear in a patient of paraquat ingestion.